The Impact of Toxic Workplace Environment, Work Role Overload, and Financial Anxiety on Workplace Stress: Islamic Workplace Spirituality as a Buffer - Rehan Sapto Rosada; Suliyanto Suliyanto; Nur Wening; Eka Pariyanti (Universitas Negeri Padang, 2026)
Lecturers in Indonesian universities frequently encounter demanding working conditions, including toxic interpersonal environments, heavy role responsibilities, and concerns about financial security. These pressures are often linked to psychological strain and reduced well-being. However, the extent to which Islamic workplace spirituality can buffer the impact of such demands remains insufficiently explored. This study examines the effects of toxic workplace environment, work role overload, and financial anxiety on workplace stress, while also testing the moderating role of Islamic workplace spirituality. A total of 220 lecturers from Indonesian higher education institutions participated in this study. Data were collected using structured questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that toxic workplace environment significantly increases workplace stress (β = .13, p = .04). Work role overload also has a significant association with workplace stress; however, the direction is negative (β = −.52, p < .001), contrary to the proposed hypothesis. Financial anxiety does not significantly affect workplace stress (β = .02, p = .36) and does not moderate the influence of toxic workplace environment on workplace stress (β = −.87, p = .07). Islamic workplace spirituality moderates the relationship between work role overload and workplace stress (β = −.23, p < .001), but it does not moderate the association between toxic workplace environment and workplace stress (β = .04, p = .31). These findings suggest that relational conditions in the academic workplace are more salient in explaining lecturers’ stress than financial concerns, while spirituality functions as a protective resource mainly for task-related pressures. The study highlights the importance of counseling support, coping reinforcement, and healthier interpersonal climates in higher education institutions.